Faktor determinan produktivitas kerja pada pekerja wanita - Widiastuti, Suci; Dieny, Fillah Fithra (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2015)
Background: Participations of women in economy activities is not the new phenomenon in Indonesia. Every years total of female workersÂ increase. However, health or nutrition status of female workers havenâ€™t gotten a good attention. This is can effect on lower productivity of female workers than male workers. Objective :This study was aimed to identify determinant factors of work productivity in female workers.Method: This study was an analytical study with cross sectional design. The selection of 40 subjects was performed by simple random sampling method. Data on energy intake was obtained from 3x24 hours food recall form. Body Mass Index (BMI) was measured with anthropometric method. Percentage body fat was measured by Bioelectric Impedance Analyzer (BIA). Haemoglobin was obtained from cyanmethemoglobin method, and data of work productivity was obtained by the comparison of sarong total that weaved succesfully by female workers during 5 work days with company target on time mentioned. The data analyzed with Shapiro wilk, rank spearman, and double linier regression.Result: Most of subjects (45%) were deficiency of energy intake. Total of 37,5% subjects were underweight. More than half of subjects (70%) were classified as normal percentage body fat. Total of 37,5% subjects were anemia, and 35% subjects were not productive. There were correlation between energy intake, percent body fat, BMI and haemoglobin with work productivity (p= 0,016; p= 0,013; p= 0,043; p= 0,000). The most correlation variable with work productivity in female workers was haemoglobin (adjusted R2 = 0,348).Conclusion: Haemoglobin had the most correlation with work productivity in female workers.